2020
DOI: 10.3390/healthcare8030266
|View full text |Cite
|
Sign up to set email alerts
|

Centralized Ambulance Diversion Policy Using Rolling-Horizon Optimization Framework to Minimize Patient Tardiness

Abstract: Ambulance diversion (AD) is a common method for reducing crowdedness of emergency departments by diverting ambulance-transported patients to a neighboring hospital. In a multi-hospital system, the AD of one hospital increases the neighboring hospital’s congestion. This should be carefully considered for minimizing patients’ tardiness in the entire multi-hospital system. Therefore, this paper proposes a centralized AD policy based on a rolling-horizon optimization framework. It is an iterative methodology for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
2
1
Order By: Relevance
“…This was addressed in Stockholm, Sweden [25] by transporting patients with respiratory symptoms to one hospital, installing intensive care units to reduce the burden on neighboring hospitals, and preventing AD during the COVID-19 outbreak. AD is also associated with a delay in prehospital time [23]. Although this study found that AD rates decreased after the intervention, an increase in the prehospital time was identified during the COVID-19 pandemic.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…This was addressed in Stockholm, Sweden [25] by transporting patients with respiratory symptoms to one hospital, installing intensive care units to reduce the burden on neighboring hospitals, and preventing AD during the COVID-19 outbreak. AD is also associated with a delay in prehospital time [23]. Although this study found that AD rates decreased after the intervention, an increase in the prehospital time was identified during the COVID-19 pandemic.…”
Section: Discussioncontrasting
confidence: 58%
“…In this study, the AD rate and prehospital time were used as indicators of intervention success. In general, AD is one way to reduce the burden on an ED by diverting patients transported by ambulance to a nearby hospital [23]. At the same time, however, AD causes overcrowding and increases the mortality rates in other EDs in the same service area [24].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, here we focus on a phenomenon strongly related to the ED overcrowding, namely the Ambulance Diversion (AD) (see, e.g. [12,13] and the references reported therein). AD is a procedure adopted by ED managers during an emergency situation, when severe patients cannot be accepted and treated anymore.…”
Section: Introductionmentioning
confidence: 99%